2019
DOI: 10.1080/10942912.2019.1656232
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic, antidiabetic and antioxidant activities of cinnamon ( cinnamomum verum ) bark extracts: polyphenol contents analysis by LC-MS/MS

Abstract: Ethanolic (EEC) and aqueous (WEC) extracts of cinnamon (Cinnamomum verum)were evaluated for their antioxidant profiles by eight distinguished bioanalytical antioxidant methods. Their inhibitory effects were tested against some enzymes including acetylcholinesterase, butyrylcholinesterase, α-glycosidase and αamylase, which linked to different diseases. Additionally, the antioxidant properties were determined and polyphenolic compositions of the both extracts were evaluated by LC-MS/MS analysis. According to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 100 publications
0
72
1
3
Order By: Relevance
“…The essential oil of this herb has been shown to have antioxidant activity. Other studies have reported antioxidant activities of water, methanol, and ethanolic cinnamon extracts [ 45 , 46 , 136 , 137 , 138 ]. This plant shows high anti-influenza virus activity [ 139 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…The essential oil of this herb has been shown to have antioxidant activity. Other studies have reported antioxidant activities of water, methanol, and ethanolic cinnamon extracts [ 45 , 46 , 136 , 137 , 138 ]. This plant shows high anti-influenza virus activity [ 139 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…Cinnamomum zeylanicum also known as cinnamon has been used for medicine and as an ingredient in Asian food. The oil extracted from Cinnamomum zeylanicum showed antioxidant, antifungal, anticancer, anti-inflammatory, antidiabetes, and antihypertensive capabilities in the previous reports (Nyadjeu et al, 2011;Varalakshmi et al, 2014;Han and Parker, 2017;Gulcin et al, 2019). It is well documented that an active constituent in a plant is varied on the method of extraction.…”
Section: Resultsmentioning
confidence: 85%
“…The breakdown of these substrates was monitored spectrophotometrically by yellow color formation of 5‐thio‐2‐nitrobenzoate anion as the result of the reaction of DTNB with thiocholine from hydrolysis of AChI or BChI with absorption at a wavelength of 412 nm. [ 52,53 ]…”
Section: Methodsmentioning
confidence: 99%